If you like et if you will : des marqueurs de discours ? - Anissa Dahak (Anglophonia)
The aim of this paper is to present the results of a corpus study of the discourse markers if you like and if you will. After a discussion of their status as discourse markers, the article focuses on the contexts where they can be found. It appears that these markers can only be used in medial and final positions. The study of the corpus sheds some light on the various functions of these markers. This paper argues that if you like and if you will have two main functions. They are first used in lexical selection or rephrasing contexts. Secondly, they appear to be downtoning (hedging) markers in that they introduce some approximation in the discourse or mitigate arguments.